Variasi Pemahaman Keagamaan Mahasiswa IAIN Surakarta - Lulu Syifa Pratama; Eko Nur Wibowo; Lia Safitriningsih; Juma'iyah Juma'iyah; Titi Nur Rohmah (Academica: Journal of Multidisciplinary Studies, 2017)
This research aims to see the various religious understanding of students in IAIN Surakarta from their activities and the existence of Islamic values in the Student Activity Unit. Even though, the study focuses on the various understanding which is moderate in term of its ideology and attitude. Using descriptive-qualitative approach, this research showed that variation of the student religious understanding at IAIN Surakarta, in term of their attitudes was moderate, which are able to be seen from their way of thinking and acting that emphasizing on the principles of tawassuth (moderate), tawazun (balance), iâ€™tidal (middle-way) and tasamuh (tolerance). In addition, the ideology of religion, which is applied by the Student Activity Unit, was also in accordance with the value of moderate understanding.Keywords:Various-understanding, Islamic-values, Moderate understanding,Â Â